ANALISIS PERSEDIAAN BAHAN BAKU PADA INDUSTRI BAWANG GORENG âMAHKOTAâ DI KOTA PALU - Sappemasse, Sappemasse; Howara, Dafina (AGROTEKBIS, 2017)
This study aims to determine the magnitude of the number of economically purchase of raw materials, the total cost of the raw materials supplies, safety stock of raw materials and when to perform re-ordering of raw materials to the industry onions Fried Onions